Beyond Convenience: Understanding E-Service Quality Role In Fostering E-Customer Satisfaction And Loyalty - Siti Yolanda Rahman Utami; Edy Yulianto; Agung Nugroho L.I.F (Jurnal Manajemen, 2024)
This research investigates the relationships between e-service quality, customer satisfaction, and loyalty within Indonesian e-commerce, explicitly focusing on the Shopee platform. Analyse 279 Shopee customers; the study examines the impact of website design, customer service, security, and fulfilment on e-service quality, customer satisfaction and loyalty. Using the purposive sampling method and SEM-PLS inferential analysis, the findings highlight the significant influence of website design on e-service quality. In contrast, customer service and security exhibit no statistically significant impact. Interestingly, efficient fulfilment emerges as a pivotal factor in enhancing e-service quality. This study underscores the significant influence of e-service quality in paving e-customer loyalty, directly or indirectly, via the mediating role of customer satisfaction. The implications of the research extend to actionable insights for e-commerce enterprises, offering strategic guidance to navigate and succeed in the competitive digital landscape of Indonesia.